Case report: Diverse immune responses in advanced pancreatic ductal adenocarcinoma treated with immune checkpoint inhibitor-based conversion therapies - Li, Xiaoying; Xiao, Chaoxin; Li, Ruizhen; Zhang, Pei; Yang, Heqi; Cao, Dan (Frontiers in Immunology, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is often diagnosed at an advanced stage, presenting limited therapeutic options and a grim prognosis due to its aggressive nature. Despite ongoing exploration of various combination therapies, a standardized treatment approach after the first-line treatment progress remains elusive. This report details the cases of two patients with unresectable advanced PDAC who underwent distinct conversion treatment regimens involving immune checkpoint inhibitors (ICIs). Remarkably, both patients became eligible for surgery following different anti-PD-1 antibody-based conversion therapies, ultimately achieving R0 resection. In essence, our findings highlight the efficacy of anti-PD-1 antibody combined with a tyrosine kinase inhibitor (TKI) regimen and chemotherapy alongside anti-PD-1 antibody as viable conversion therapies for preoperative advanced PDAC. Tumor immune microenvironment (TIME) analysis underscores the intratumoral and intertumoral heterogeneity observed in the postoperative immune landscape of surgical specimens. This insight contributes to a deeper understanding of the potential benefits of these conversion therapies in addressing the challenging landscape of advanced PDAC.